El incumplimiento del principio de eficiencia y el delito de cohecho en la administración pública en el Ecuador - Pacheco Proaño, Alex German (2025)
This study aimed to analyze the relationship between the failure to comply the principle of efficiency and the commission of the bribery crime in public administration in Ecuador. The problem was addressed through a thorough review of the literature and the analysis of relevant cases from a qualitative approach focused on the interpretative analysis of legal documents and the collection of data by the means of interviews with a non-experimental research design. The failure to comply the principle of efficiency was identified which facilitated the emergence of corrupt practices by creating an environment prone to the lack of transparence and inefficient bureaucracy. Additionally, the administrative inefficiency contributed to the proliferation of the bribery crime by allowing processes that did not provide an adequate control and an effective accountability. It was concluded that the improvement in the efficiency of administrative processes could significantly reduce the opportunities to commit bribery.